Analysing the Twitter social media network in voicing opinions on money loundering issue in Indonesia - Prayudi Prayudi; Muhammad Edy Susilo (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
This study aims to examine the Twitter social media network concerning the money laundering issue involving the Indonesian Ministry of Finance. The primary goal is identifying and highlighting the individuals or entities significantly influencing online discussions. Further, the study looks at the intricacies of public perception and communication about this pressing issue within the Ministry. The study gathered and analyzed Twitter data using social network analysis methodologies, consisting of 6742 nodes and 744 edges. The findings demonstrate ten actors exhibit the most prominent clusters, whereas five exhibit the maximum links. The significance of the Twitter user was @seeksixsuck, who highlights the importance of religious people in ongoing conversations. This research study enhances the social media environment's comprehension of money laundering within the Ministry of Finance, providing insights into the interconnected relationships and individuals influencing the ongoing conversation. The study's findings provide significant value in facilitating public engagement initiatives and promoting a more knowledgeable and engaged population in the ongoing battle against money laundering.